If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11(v+4)-2v=3(3v+1)-9
We move all terms to the left:
11(v+4)-2v-(3(3v+1)-9)=0
We add all the numbers together, and all the variables
-2v+11(v+4)-(3(3v+1)-9)=0
We multiply parentheses
-2v+11v-(3(3v+1)-9)+44=0
We calculate terms in parentheses: -(3(3v+1)-9), so:We add all the numbers together, and all the variables
3(3v+1)-9
We multiply parentheses
9v+3-9
We add all the numbers together, and all the variables
9v-6
Back to the equation:
-(9v-6)
9v-(9v-6)+44=0
We get rid of parentheses
9v-9v+6+44=0
We add all the numbers together, and all the variables
50!=0
There is no solution for this equation
| -4(1y+-4y)+3=-3(2y-1y)+1+14y | | 15k=20 | | X+1/14=6/7+x-7/9 | | 427.75=t^2+55t | | (x-5)(x-5)-121=0 | | (x-5)^2-121=0 | | 3(12-5y)=9(2-y)+6(3-y) | | 188=13(s-55)+45 | | y=5(850)-1000 | | 6(7.5-1y)-y=-4 | | 5y-1=4y-5 | | y=-(850)+2000 | | y=-5(850)+3500 | | 9/4x-6=28.5 | | y=(850)-1000 | | y=5(850)+1000 | | y=0.42×64T | | 4(0)-5x=10 | | 7^3x=8^2x | | x+4/2-6=2x-8/3 | | -3y+5(1y-1)=7-6(7-y) | | 4x-5(0)=10 | | -4(y-4y)+3=-3(2y-y)+1+14y | | .2x=x-212 | | x^2-121x+120=0 | | 7+3x=9x-11 | | 8(2n+2)=8(8n+4)+9 | | 2x+10+4-36+4x-34=180 | | x/2+x/3=x/6+4 | | 6x/11=5x/8-7 | | 5(x-3)=17-3x | | 10x+14−4x=−8x−5+x |